2014
DOI: 10.1016/j.vaccine.2014.03.091
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient production of a dengue pseudoinfectious virus

Abstract: Dengue is a major infectious disease that affects people living in tropical and subtropical regions around the world. The causative agents are dengue virus serotype 1, 2, 3, and 4 (DENV1, 2, 3, and 4). Developing a vaccine for dengue is a high priority for public health, but traditional methods have faced numerous obstacles due to the unique immunopathogenesis of dengue virus infection. Here, we report a novel dengue vaccine candidate based on dengue pseudoinfectious virus (PIV) produced by the incorporation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Exploitation of these post-translational control measures has facilitated the continuing development of novel vaccines and therapeutics for use against flavivirus infections (Goto et al, 2005;Keelapang et al, 2013;Ohtaki et al, 2010;Pang et al, 2014;Roby et al, 2011Roby et al, , 2013Roby et al, , 2014Zhang et al, 2011).…”
Section: Flavivirusesmentioning
confidence: 99%
See 2 more Smart Citations
“…Exploitation of these post-translational control measures has facilitated the continuing development of novel vaccines and therapeutics for use against flavivirus infections (Goto et al, 2005;Keelapang et al, 2013;Ohtaki et al, 2010;Pang et al, 2014;Roby et al, 2011Roby et al, , 2013Roby et al, , 2014Zhang et al, 2011).…”
Section: Flavivirusesmentioning
confidence: 99%
“…Thus, recent investigations by our and other groups have built on the discoveries of Lobigs et al (2010) to create constructs in which an anchored form of C should still be cleavable by NS2B/3 in the absence of downstream prM. Constructs with trans-C genes extended to either include the signal sequence and the first 10 codons of prM (Roby et al, 2014), or the entire sequence of the pr peptide (Pang et al, 2014), were generated and shown to be highly efficient at both infectious and non-infectious particle secretion, thus representing attractive candidates for future vaccine development.…”
Section: Post-translational Modification Of Structural Proteins In Vamentioning
confidence: 99%
See 1 more Smart Citation
“…True to the SRIP name, these particles can invade cells and release the replicon RNA to the cytoplasm, followed by initial RNA replication but inability to form infectious virions because of the lack of a functional copy of the structural gene in the genome [82] , [83] , [84] ; however, the cells infected by SRIP-packaged ΔC replicon RNA should produce a mass of SVPs. To date, different expression systems have been used to package the ΔC replicons of WNV [85] , YFV [86] and DENV2 [87] , [88] to produce SRIPs.…”
Section: Rational Vaccine Design Targeting Capsid Proteinmentioning
confidence: 99%
“…Replicating pseudo-infectious vaccines with large internal deletions within the C gene offer the combined benefit of the safety of non-infectious vaccines (they cannot package RNA and thus form a spreading infection) as well as the robust immune response generated by the replication of live vaccines (Roby et al , 2011). This approach for vaccine creation has been investigated by a number of groups and has led to the successful generation of protective vaccine candidates against a number of pathogenic flaviviruses (Ishikawa et al , 2008; Kofler et al , 2004; Mason et al , 2006; Pang et al , 2014; Roby et al , 2011; 2013; Rumyantsev et al , 2013; Seregin et al , 2006; Suzuki et al , 2009; Widman et al , 2008). Initial iterations of this strategy consisted solely of C-deleted flavivirus genomes delivered to cells/animals as nucleic acid either directly as cDNA copies (Seregin et al , 2006) or as in vitro transcribed RNA (Kofler et al , 2004).…”
Section: Introductionmentioning
confidence: 99%